Identifikasi Polimorfisme Titik -1082 Promoter Gen IL-10 pada Penderita Kusta - Oktariana, Desi; Argentina, Fifa; Lusiana, Evi; Tamzil, Nia Savitri (Sriwijaya Journal of Medicine, 2020)
Leprosy is a chronic disease caused by Mycobacterium lepraeinfection, which affects skin and nerves, then can result in disability. Interleukin-10 have an important role in the pathogenesis of leprosy. Polymorphism in this gene promoter is thought to affect IL-10 production, which can then influence the process of microbial elimination in the development of leprosy. One of the most common polymorphisms associated with IL-10 is the polymorphism of the -1082 on the gene promoter. The purpose of this study was to identify the polymorphism of the -1082 interleukin-10 gene promoter in leprosy patients treated at RSUP dr. Mohammad Hoesin Palembang. This research is an observational descriptive study with cross sectional design. Polymorphism of -1082 interleukin-10 gene promoter was measured by PCR-RFLP method, electrophoresis, and visualized in UV light. From this study it was found that the frequency distribution of genotype AA was 80%, AG was 14%, and GG was 6%. The frequency distribution of allele A is 87% and allele G is 13%. Wild type genotype is more common in leprosy sufferers (80%).